Cold exposure and musculoskeletal conditions; A scoping review - Farbu, Erlend Hoftun; Höper, Anje Christina; Reierth, Eirik; Nilsson, Tohr; Skandfer, Morten (Frontiers in Physiology, 2022)
Background: Musculoskeletal conditions are major contributors to years lived with disability. Cold exposure can be a risk factor, but any conclusion is obscure. Aim: The aim of the present scoping review was to identify the existing evidence of an association between cold exposure and musculoskeletal conditions. The aim also included to consider pain in different regions and their assessment, as well as different measures of cold exposure, effect sizes, and to assess the feasibility of future systematic reviews and meta-analyses. Eligibility criteria: The studies must have: an epidemiological design, defined cold exposure to come prior to the health outcome, defined exposure and outcome(s), existence of effect estimate(s) or data that made it possible to calculate such an estimate. Further, studies were required to be in English language and published in peer-reviewed journals. Studies that had a specific goal of studying cold exposure as an aggravator of already existing health problems were excluded. Sources: We searched Ovid MEDLINE(R) and Epub Ahead of Print, In-Process & Other Non-Indexed Citations, Daily and Versions(R), and Embase Classic+Embase for original studies. Charting method: The included studies were reviewed for study population, measurement of exposure and outcome, and effect size. Each publication was assessed for risk of bias. Results: The included studies were heterogeneous in populations, measures of cold exposure and musculoskeletal conditions. Most studies used self-reported data. They were mostly cross-sectional studies, only two were prospective and one was a case-control study. Associations were found for different cold exposures and regional musculoskeletal conditions, but the heterogeneity and lack of studies impeded valid synthesis of risk magnitude, or meta-analyses. Conclusion: The studies identified in this review indicate that cold exposure increases the risk of musculoskeletal conditions. However, there is a need for studies that better assess temporality between exposure and outcome. Future studies should also include better exposure assessment, including both objective measurements and measures of subjective experience of cold exposure. The heterogeneity in measurement of exposure and outcome impeded any meta-analysis.